Birth order and maternal ratings of infant temperament - Keresteš, Gordana (2006)
The study examined birth order effects on maternal ratings of infant temperament. Mothers of 120 fullterm infants (55 boys, 65 girls) completed the Rothbart Infant Behavior Questionnaire (IBQ) when their infants were 6 or 12 months old. There were 49 mothers of firstborns and 71 mothers of laterborns. A 2 (infant birth order) by 2 (infant gender) analysis of covariance was performed on the scores for each of the six IBQ scales, with maternal age included as a covariate. A significant main effect for birth order was found on the Fear scale of the IBQ, with firstborn infants being rated by their mothers as less fearful than laterborns. Birth order effects on other IBQ scales were insignificant. Child’ s gender had neither main nor interaction effects with birth order on temperament scores. Additional analyses showed that in the subsample of laterborns spacing from the older sibling also had no influence on maternal ratings of temperament. The results were situated in the field of birth order research and discussed from a developmental perspective. The need to employ more sophisticated research designs in future birth order studies was emphasized.
Projekt MZOS
ENG